Municipal plan of adaptation to climate change of Cabanas 2019 - 2023 (Copan - Honduras) - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
The plan, developed with Resca bilateral project of CCAFS, defines strategic actions for adaptation to climate change in the municipality of Cabanas in the department of Copan (Honduras).